2019
DOI: 10.20944/preprints201909.0063.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational Tools in the Discovery of FABP4 Ligands: A Statistical and Molecular Modeling Approach

Abstract: Small molecule inhibitors of adipocyte fatty-acid binding protein 4 (FABP4) have got interest following the recent publication of their pharmacologically beneficial effects. Recently it comes out that FABP4 is an attractive molecular target for the treatment of type 2 diabetes, other metabolic diseases, and some type of cancers. In the past years, hundreds of effective FABP4 inhibitors have been synthesized and discovered but, unfortunately, none of them is in the clinical research phase. The field of computer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…A previous study has shown that Phe19, Met20, Ala33, Pro38, Lys58, Phe57, Ala75, Glu72, Arg106, and Arg126 are important amino acid residues in the interaction process between FABP4 and its [11]. The presence of mutations in Phe57 residue shows a decrease in the binding function of the FABP4 protein to fatty acids, indicating the important role of this residue in FABP4 function.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A previous study has shown that Phe19, Met20, Ala33, Pro38, Lys58, Phe57, Ala75, Glu72, Arg106, and Arg126 are important amino acid residues in the interaction process between FABP4 and its [11]. The presence of mutations in Phe57 residue shows a decrease in the binding function of the FABP4 protein to fatty acids, indicating the important role of this residue in FABP4 function.…”
Section: Discussionmentioning
confidence: 95%
“…The smaller binding energy value between testing ligands and proteins, the better the binding affinity and the more stable the interaction between complexes [10]. The position of testing ligands is indicated by the amino acid residues surrounding the ligands, while the ligand affinity to its receptor can be seen from the interaction between the ligands (native and testing ligands) with the amino acid residues that are responsible for the catalytic side of each protein [11].…”
Section: Discussionmentioning
confidence: 99%
“…While the computer-aided structure-based drug design (e.g., docking) depend on the actual 3D structure of the targeted binding site of the targeted receptor protein to understand the stabilizing interactions at the molecular level between the studied ligand/receptor system, the ligand based-drug design (e.g., 3D-QSAR modeling) approach relies on the recognition of a database of already know ligands interacting with the studied target receptor. Both structure and ligand bases technologies have several success stories and pursue a key role in the drug modern drug discovery process [9][10][11][12][13]. In this context, several of these approaches have been recently employed to research novel drug candidates against COVID-19.…”
Section: Introductionmentioning
confidence: 99%